Building Democracy for Women and Sexual Minorities: Union Embrace of Diversity - Hunt, Gerald; Haiven, Judy (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 2006)
This article assesses Canadian labour’s response to changed demographics by considering the way unions have engaged with women and sexual minorities (gay, lesbian, bisexual and transgendered people). Many unions have now adopted inclusive policies. However, to consider how effectively these policies have been articulated and implemented at the local level, we consider two illustrative cases. One case involves a serious breakdown at the local level over pay equity for women; another case tells the story of a local’s support for a gay man’s challenge to a school board. We conclude that labour’s apparent formal recognition of women and sexual minorities has not necessarily diffused into effective accommodation locally, although we also find grounds for optimism.